TWITCH AND SHOUT! - Andersen, Hans Harrestrup (Tidsskriftet Antropologi, 2001)
T he noble art of seeing as many species of birds as possible, has become a widespread trend among birdwatchers worldwide. The author is no exception. He discusses the motives, ups and downs and psycological aspects of this peculiar pastime.